Flame retardant and antimicrobial paper coatings with rosemary oil and barium borate - URAL, ELİF (My University, 2022)
© 2022, Publishing House of the Romanian Academy. All rights reserved.Adding an antimicrobial effect to the papers used in the cardboard packaging industry can extend the life of the packed product. Paper, due to its structure, has the property of being ignited quickly. Enhancing the properties of paper, the combination of antimicrobial protection, low flammability and good printability to the paper will expand its usage area in the packaging industry. In this study, barium borate was synthesized in order to impart low flammability to paper. Different combinations of rosemary oil and barium borate were mixed with binding starch in varying amounts, and formulations were prepared. With these mixtures, 80 g/m2 paper was coated using a laboratory-type paper coating machine. The antimicrobial properties of the paper were investigated by performing the disk diffusion antimicrobial test against E. coli and S. aureus bacteria. The Limiting Oxygen Index (LOI) test was performed to determine the low flammability of the paper. Color, gloss, contact angle and surface energy tests were performed for the printability properties of the paper. As a result, the coatings containing formulations of barium borate and rosemary oil, applied to the paper surface, succeeded in imparting antimicrobial and low flammability properties to the papers, while also improving the printability features.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Organik Kimya; Fizik Bilimleri; Malzeme Kimyası; Organic Chemistry; Physical Sciences; Materials Chemistry; Active packaging; Antimicrobial coating; Flame retardant; Paper coating; Printability